Konstruksi Alat Ukur Nasionalisme sebagai Nilai Kejuangan Jenderal Achmad Yani - Egi Prawita; Dian Juliarti Bantam; Davit Bagus Triyantoro; Deni Santi Pertiwi (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2025)
Universitas Jenderal Achmad Yani Yogyakarta has value namely Nilai-Nilai Kejuangan Jenderal Achmad Yani. One of the values is Nasionalisme. Nasionalisme is individual ability to carry out tasks and achieve goals based on awareness and a spirit of love for the homeland, having pride as a nation, maintaining national honor, and having a sense of solidarity This study aims to construct Nasionalisme scale based on Nilai Kejuangan Jenderal Achmad Yani trough Universitas Jenderal Achmad Yani Yogyakarta students. This scale is valid and reliable. The content validity and construct validity used in this scale. The content validity using Aiken’s V coefficient around 0,57 to 0,90. This scale also has fit model for confirmatory factor analysis. The final reliability of this scale using the Cronbach Alpha reliability coefficient which is 0,802. From 15 items, there are 2 items has poor quality, namely item number 1 and 14.